Effect of physical-kinesthetic intelligence exercises on developing motor abilities and basic skills of basketball in female students - Mashkoor, Najat Baqir; Hameed, Nagham Hateem (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The learning process needs an appropriate method and technique to be implemented among the players. The basketball game contains a set of skills that need a close relationship between actions, neurological, mental and muscular abilities and the control of bodily movement. One of the important factors in learning, improving and developing motor abilities and learning the skill as well as the planning performance is through learners’ ability to analyze, plan and solve problems in learning processes. The physical intelligence created by the theory of intellectual development is one of the types of intelligence that must be taught to the learners to develop basic basketball skills, that need to be controlled, compatible and balanced during the performance of the skills, including shooting skills in basketball ring. The primary aim of the present study was to identify the levels of physical intelligence and to find out the significant difference between the pre and post-tests in the physical intelligence, motor abilities and basic skills between the experimental and control group. The present study had an experimental study design. The research “community” was determined from the students of the fourth school stage (grade 9) of Al-Amal High School for Girls in Baghdad for the academic year 2019-2020. A total of 20 students were recruited as sample participants for the study, who represented 11.29% of the total population. The participants were allocated into two groups, i.e. experimental group and the control group. The participants of the experimental group received training with physical intelligence exercises, whereas control group participants received training with the traditional method.